Role of social support for pregnant women in maternal and postpartum care - Janik-Fuks, Inga; Maciejewska, Martyna; Korabiusz, Katarzyna; Wawryków, Agata; Wilczyńska, Agnieszka; Stecko, Monika; Fabian-Danielewska, Anna (Journal of Education, Health and Sport, 2019)
Pregnancy, childbirth and postpartum care is special time in woman’s life. Often those moment cause many different emotions, both positive and negative. Mothers-to-be are often scared of childbirth, with following strong fear for life and health of their baby. The very moment of delivery can be special experience, unfortunately not always pleasant. This is why there is special note given to the role of social support as factor enhancing the proces of adaptation to the new role. Adequate support can reduce fear of childbirth, reduce probability of postpartum depression and enhance proper mother – child interaction.